Sustainable development of the Polish meat industry after accession to the European Union - Tereszczuk, Mirosława; Mroczek, Robert (European Journal of Sustainable Development, 2014)
The last decade, i.e. 2003-2013, was a period of intensive development of the Polish meat industry, in which Poland’s accession to the European Union definitely had its share. The meat industry in Poland has been developing faster that in the EU-15 and Poland was the leader of EU-12. The EU integration had a positive impact on accelerating the production growth in the Polish meat industry, and several years of the process of adjustment to the EU requirements significantly changed the image of the Polish meat companies on the common European market. The Polish meat industry became a significant food producer on the European market (in 2012 fourth place in the EU) and the Polish meat processing plants are recognised as some of the most advanced in the EU. One of the main factors of meat industry development in Poland in the past decade was its very fast development. Key words: sustainable development, meat industry, meat products, export, import